Procalcitonin and C‐reactive protein for diagnosing post‐operative sepsis in neonates. (12th October 2021) - Rao, Hitendra; Dutta, Sourabh; Menon, Prema; Attri, Savita; Sachdeva, Naresh; Malik, Muneer
Abstract : Aim: To determine whether serum procalcitonin (PCT) or C‐reactive protein (CRP) can diagnose post‐operative sepsis among neonates undergoing major non‐cardiac surgery. Methods: In this diagnostic study, we included neonates who underwent major non‐cardiac surgery and were monitored for post‐operative sepsis. We excluded pre‐existing septic, inflammatory or life‐threatening conditions. Subjects either had 'definite' (culture‐positive, n  = 14), 'probable' (clinical sepsis, culture‐negative, n  = 25) or no sepsis ( n  = 31). We measured serum CRP and PCT at 48 ± 6 h, 72 ± 6 h and 96 ± 6 h post‐operatively and compared 'definite or probable sepsis' with 'no sepsis'. Results: Median (Q1, Q3) CRP (mg/L) in 'definite or probable' sepsis group was higher than 'no sepsis' at 72 h (91.48 (57.87, 143.50) vs. 51.32 (33.0, 80.1); P  = 0.009) and 96 h (87.51 (45.19, 128.22) vs. 31.00 (25.3, 45.2); P  < 0.001). Median (Q1, Q3) PCT (ng/mL) in 'definite or probable' sepsis was higher than 'no sepsis' at 72 h (4.22 (2.04, 12.73) vs. 1.78 (0.9, 6.4); P  = 0.01) and 96 h (3.54 (1.96, 9.65) vs. 0.97 (0.4, 3.0); P  < 0.001). Ninety‐six‐hour CRP and PCT cut‐offs (based on Youden's index) were 74.16 mg/L and 1.65 ng/mL, respectively. If both CRP and PCT were positive, specificity was 100% (95% confidence interval: 88.78–100). If either one was positive, sensitivity was 88.89% (95% confidence interval: 73.94–96.89). Conclusions: Septic neonates have significantly higher serum CRP and PCT compared to non‐septic neonates at 72 and 96 h post‐operatively. If both CRP and PCT are positive at 96 h after surgery, it has 100% specificity, and if either one is positive, 89% sensitivity.